Development Of Leishmania Tarentolae Expression Systems For Different Recombinant Antibody Formats - Jing Yi, Lai (2024)
Production of recombinant antibodies has been an important topic for biomedical applications. Currently, expression of monoclonal antibodies is mainly performed using mammalian cell lines such as Chinese hamster ovary (CHO) cells and Human embryonic kidney 293 (HEK293) cells due the advantage of human-like post-translational modifications. However, the use of mammalian cell lines has some drawbacks especially in term of cost. The introduction of Leishmania tarentolae as an expression host is viewed as an interesting alternative due to their post-translational modification, which is similar to human but is more cost-effective for expression and maintenance. In this study, the use of L. tarentolae was explored as a platform to express recombinant antibodies in scFv-Fc and IgG format. A single chain fragment variable (scFv) clone against long-chain neurotoxin (LNTX) of Naja kaouthia was identified from naïve human antibody library. The clone was expressed and characterized in Escherichia coli as scFv and further converted to scFv-Fc and IgG format for expression in L. tarentolae. The expression of IgG was achieved using a bicistronic vector system. A total of two constructs, encompassing both possible position of the heavy chain (HC) and light chain (LC), were expressed. The construct with the HC-LC gene arrangement was found to perform better in term of yield. The stability of the IgG at 26ºC and 45ºC was also examined. While the expression performance of antibody clone is dependent on the antibody gene sequence, the study shows the potential application of L. tarentolae for expressing both scFv-Fc and IgG. In conclusion, the L. tarentolae expression system can be touted as a possible alternative system for the expression of scFv-Fc and IgG antibody clones.